Regulatory role of NADPH oxidases in symbiosis and dysbiosis in the sea anemone Aiptasia - Sawiccy, Valeri; Tjandra, Noah W.; Maruyama, Shumpei; Ruggeri, Maria; Vo, Candice; Harmon, Lily A.; Poole, Angela Z.; Weis, Virginia M. (Frontiers in Marine Science, 2025)
The endosymbiosis between cnidarians and photosynthetic dinoflagellates of the Symbiodiniaceae family forms the foundation of coral reef ecosystems. Prolonged environmental shifts can disrupt the cnidarian–Symbiodiniaceae partnership, triggering dysbiosis and coral bleaching and ultimately resulting in coral starvation, mortality, and the collapse of reef ecosystems. Despite its significance, critical gaps remain in our understanding of the cellular mechanisms governing symbiosis and dysbiosis. Innate immune genes and pathways are highly conserved across the Metazoa, including in cnidarians. Among these is NADPH oxidase (NOX), a key enzyme responsible for generating reactive oxygen species (ROS), primarily for microbial degradation within phagolysosomes. In this study, we hypothesize that NOX plays a role in the regulation of cnidarian–Symbiodiniaceae symbiosis and the host phagosomal maturation process. We investigated NOX function in relation to symbiotic state and heat stress in the sea anemone Exaiptasia diaphana (commonly called aiptasia), a model for cnidarian–Symbiodiniaceae symbiosis and dysbiosis. Our findings show that NOX gene and protein expression is suppressed in the symbiotic state, supporting the hypothesis that symbionts modulate host innate immunity. However, upon heat treatment, we observed increased NOX expression and activity along with NOX localization around algal symbionts, suggesting that host phagosomal maturation processes are engaged during bleaching. We propose a model where the phagocytic NOX complex becomes activated during symbiosis breakdown and bleaching. Our findings support the hypothesis that in situ degradation, facilitated by ROS generated by NOX, plays a key role in the process of dysbiosis. This work contributes to our understanding of cnidarian innate immunity, highlighting critical steps in dysbiosis and phagosomal maturation processes within cnidarian–Symbiodiniaceae symbiosis.